Fuzzy Semimaximal Submodules - A. Hamel, Maysoun; Y. Khalaf, Hatam (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2020)
Let R be a commutative ring with unity and an R-submodule N is called semimaximal if and only if the sufficient conditions of F-submodules to be semimaximal .Also the concepts of (simple , semisimple) F- submodules and quotient F- modules are  introduced and given some  properties .